PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN PELANGGAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MODERASI DI PT SINARMAS SENTRA CIPTA - Yani, Ari Soeti; Sinambela, Yuni Fratika (JURNAL ILMIAH EDUNOMIKA, 2024)
This aims of this research was to assess the impact of service quality, customer trust and customer satisfaction on customer loyalty at PT Sinarmas Sentra Cipta. Quantitative data collection techniques are conducted through online survey offerings. In this study, 100 samples were collected using a targeted sampling strategy. The results of this study show a quality of service T-Statics score of 2.021 > T-Table score of 1.96, and a P-value of 0.043 > 0.05, which is positive and significant. The t statistic for customer retention rate is 3.282 > t table value is 1.96 and the p-value is 0.001 > 0.05, indicating positive and significant. T-statistic 11.802 > T-table value 1.96, P-value 0.000 > 0.05. As a result, customer satisfaction reduces customer confidence in customer loyalty, which benefits PT Sinarmas Sentra Cipta.Â